Crescimento econômico e inovação : uma estimativa da fronteira de possibilidades de inovação - Canci, Ediane (2016)
This dissertation investigates the format of Innovation Possibilities Function to the United States in the period of 1950 to 2011. Is used the theoretical model of Kennedy (1964) for the estimation of an econometric model series time between the growth rates of labor productivity and capital. The database used was the United States Long Term - USLT organized by Dumenil and Levy (1994). The results suggest that the Innovation Possibilities Function is compatible with the description of technical progress happened during the analysis period and point the existence of a trade-off between the growth rates of labor productivity and capital to the United States in the period in study.